Analysis Of Readiness For Merdeka Curriculum Implementation: Case Study In Sd/Mi In Lombok Tengah Regency - Hikmah Ramdhani Putri; Arif Widodo; Fitri Puji Astria; Umar Umar; Hasnawati Hasnawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The Merdeka Curriculum has been implemented nationally starting in the 2021/2022 school year by schools participating in the driving school program. Gradually in the following years, each educational unit can choose to implement an merdeka curriculum according to their respective readiness. The government has prepared standard levels of readiness to implement the merdeka curriculum which consists of 4 levels. The first level is called the initial stage, the second level is called the developing stage, the third level is called the ready stage, and the fourth level is called the advanced stage. This research aims to determine the level of readiness of SD/MI in implementing the merdeka curriculum. This research uses a qualitative research method with a case study approach. Data collection uses observation, questionnaires and interviews. The subjects of this research were 18 SD/MI in Lombok Tengah regency. The sources of information in this research are school principals and teachers. The research results show that the majority of SD/MI are still at the second level of readiness, namely at the developing level, only a few schools are at the ready and advanced level. Based on the results of this research, it is recommended for policy makers to carry out an evaluation so that the level of school readiness in implementing the merdeka curriculum can increase